Safety and efficacy of extended release ketamine tablets in patients with treatment-resistant depression and anxiety: open label pilot study - Paul Glue; Natalie J. Medlicott; Shona Neehoff; Peter Surman; Fred Lam; Noelyn Hung; Cheung-tak Hung (SAGE Publishing, 2020)
Background: Ketamine's defining side effects are dissociation and increased blood pressure/heart rate. An oral formulation with delayed absorption could minimize these effects. We recently reported safety and tolerability data for an extended release ketamine tablet in healthy volunteers. Methods: To assess safety, tolerability, efficacy, and pharmacokinetics of an extended release oral ketamine tablet in patients with treatment-resistant depression/anxiety. This was a multiple dose open-label flexible dose uncontrolled study in seven patients with treatment-resistant depression/anxiety, who had all previously demonstrated mood improvement to subcutaneous ketamine. Assessments included ratings of anxiety, depression and dissociation, safety and tolerability, and blood samples for ketamine pharmacokinetics and brain-derived neurotrophic factor (BDNF) concentrations. Results: Improvements in anxiety and depression ratings occurred gradually over 96 h; all patients had >50% improvements in mood ratings. Ketamine was safe and well tolerated, with no changes in vital signs, and a single brief report of dissociation. Ketamine may induce its own metabolism, as the ratio of norketamine to ketamine increased out to 96 h. Serum BDNF concentrations did not change during the study. Conclusion: Ketamine's safety/tolerability may be improved with an extended release oral formulation. Onset of mood improvement is slightly delayed compared with parenteral dosing. These data support the further development of extended release ketamine tablets for treatment of resistant depression and anxiety disorders.